Russia's National Security Policy in Facing the Dynamics of Threats and Global Challenges: a Critical Analysis - Kaunang, Elfira Sylviani; Timur, Fauzia G. Cempaka; Perwita, Anak Agung Banju; Siswoputro, Suspada (PT FORMOSA CENDEKIA GLOBAL, 2024)
Every country definitely has goals and interests in maintaining its existence. In making this happen, countries often face challenges and threats that can cause failure to achieve goals. This article discusses the important role of Russia's National Security Policy in responding to the country's threats and challenges. The main focus of the articles includes the current analysis of global geopolitical dynamics, changes in security threats, and steps taken by the Russian government. Through a cross-sector literature approach, this article analyzes the newest security policies and strategies implemented by Russia to protect its sovereignty, sovereign rights, territorial integrity, and national integrity and unity. The use of economic power, military resources, diplomacy, and cyber security policies are the focus of research to measure a country's effectiveness and responsiveness to evolving threats. This article aims to provide in-depth insight into the role of Russia's National Security Policy in maintaining stability, security, and national interests amidst ever-changing geopolitical dynamics.